Posbindu Cadres Art Dance Therapy (PodCAsT) Improving the Quality of Life - Wibawa, Shinta; Kustanti, Anita; Septiyaningtyas, Shyalva Ika; Hidayati, Fahmi (Alta Dharma Publisher, 2024)
Background: Stress is something condition disease no contagious as possible give an impact bad for health when keeps going experienced by someone for period long. Dancing could be fun for Posbindu Cadres but also could help promote relaxation to reduce stress. Objective: This study aims to uncover the effectiveness of Posbindu Cadres Art Dance Theraphy (PodCAsT) for Posbindu Cadres in reducing stress. Method: The study was a quasi-experimental research with a one-group pretest-posttest design. Twenty-Eight cadres at Gading Wetan Donokerto, Sleman, Yogyakarta, Indonesia were participated the study. Level of Stress was measured using the Hamilton Anxiety Rating Scale (HARS). Data were analyzed using the Wilcoxon test. Result: There was a significant difference with (p<0.001) between the stress level on cadres before and after Posbindu Cadres Art Dance Theraphy (PodCAsT) with with the stress level from 30 to 11. Conclusion: The PodCAsT could effectively reduce the level stress of cadres who experience stress with severe anxiety because of the many duties and responsibilities carried out by Posbindu Cadres in serving and monitoring and controlling public health.Implication: Posbindu Cadres Art Dance Therapy (PodCAsT) can be applied in communities, especially communities, to improve the quality of life and at the same time maintain Yogyakarta traditional dancing culture